IMPROVED ALGORITHM FOR QUASI-STATIC SOLUTION OF HIGH SPEED ANGULAR CONTACT BALL BEARING - GAO Feng; HE PingPing; LI Yan; SHUI LinQi (Jixie qiangdu)
The quasi-static model of angular contact ball bearing is established using no raceway control hypothesis to analyze the motion status of bearings. An improved Newton-Raphson algorithm is proposed to deal with the problems of determination of the initial value difficultly,the iterative process not easily to converge and the slow convergence rate which are arisen out while the quasi-static model solved by the traditional Newton-Raphson algorithm. Firstly,the intermediate variables are introducd to reduce the number of unknowns and the nonlinear equations are solved with step algorithm by which it’s ease to select the initial value. Secondly,the iterative correction factor optimized by bisection method is used to improve NewtonRaphson algorithm by which the convergence time is shortened. Finally,the solution process of the Jacobi matrix is simplified through the matrix transformation. The calculation results of the B7008 C bearing shows that the proposed algorithm is superior to the traditional algorithm and can effectively decrease the difficulty to solve the quasi-static model of the angular contact ball bearing with higher convergence.